Pengaruh Kepemimpinan terhadap Disiplin Pegawai.pada.Dinas Perindustrian,dan Perdagangan Provinsi Jambi - Khuluqon Azima (Universitas Batanghari Jambi, 2022)
In this study, the aim is to find out whether there is a significant influence on the leadership variable on employee discipline at the Jambi Province Industry and Trade Office. The object of research in this study is the entire population of 130 employees, with the data sources obtained from direct respondent questionnaires and also literature studies and other external data. This study uses quantitative descriptive analysis and the data is processed using SPSS 24, namely with simple linear regression analysis. The results showed that the regression equation was Y=1.704 + 0.517X + e. Then the value of the coefficient of determination (R2) is 0.374, which means that the leadership variable (X) is able to explain the discipline variable (Y) at the Jambi Province Industry and Trade Service of 37.4% while 62.6% is influenced by other variables outside of the variables already defined. researched. And partially the magnitude of the influence of the leadership variable is 8.744 and ttable is 1.979. from the comparison results, it can be seen that tcount is greater than ttable (tcount > ttable). With that Ho is rejected and Ha is accepted. By comparing the number of significant levels (sig) of research with a significant level of 0.05 then 0.000 <0.05, so it can be said that there is a significant influence between the leadership variables on the discipline of the Jambi Province Industry and Trade Office.